PENCIPTAAN LAYANAN PRIMA MELALUI PENERAPAN SISTEM INFORMASI MANAJEMEN DI PERPUSTAKAAN IAIN PURWOKERTO - Diyasika Ulinafiah; Novan Ardy Wiyani (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
This study aimed to find out how the Creation of Excellent Services through the application of Management Information Systems at the IAIN Purwokerto Library. This study has a qualitative approach with the conclusion that the Creation of Excellent Services through Management Information Systems in the Purwokerto IAIN Library cannot be separated from the theory of management functions, namely planning, organizing, implementing, and monitoring. The management functions that are applied in the Creation of Excellent Services through the implementation of Management Information Systems are as follows (1) Planning, procurement of Management Information System devices, even though they already exist but continue to be developed in supporting excellent services. (2) Organizing, through the implementation of a Management Information System that runs well because of the support of qualified human resources in each field, so that the use of tools or software can be in accordance with its function. (3) Implementation, excellent services run in accordance with operational standards, especially the use of Management Information Systems support the improvement of Prime Services in the Library. (4) Supervision, carried out by the head of the library by reviewing the performance of excellent service both direct supervision and indirect supervision.